Alarming rise in prevalence of obesity among children with essential hypertension: Reflection of larger global epidemiological change of adolescent nutritional status - Vishwak Gundeti; Shrikiran Aroor; Koushik H; Leslie E. Lewis; Suneel C. Mundkur; Ramesh Bhat Y; Pushpa Kini (Clinical Epidemiology and Global Health)
Background: Young-onset hypertension is emerging as a substantial public health issue globally, especially in children and adolescents. The rising incidence of essential hypertension in pediatric populations is chiefly attributable to changes in lifestyle and obesity. Aim: This study assesses the clinical characteristics, risk factors, and causes of hypertension in children aged 1 month to 18 years with a focus on essential hypertension and obesity. Methods: A prospective observational study was undertaken at the Department of Paediatrics of a tertiary care medical college in Southern India from October 2022 to July 2024. The research encompassed 116 children aged 1 month to 18 years admitted with hypertension, diagnosed as per 2017 American Academy of Pediatrics (AAP) guidelines. Data encompassing demographic information, familial history - risk factors for hypertension, anthropometric parameters, and clinical characteristics were gathered. Details of diagnostic evaluations conducted, comprising blood tests, imaging studies, and hormonal analyses were analyzed. Results: The prevalence of hypertension among the admitted children during the study period was found to be 1.6 %. Renal parenchymal disorders accounted for the major cause of hypertension (68.9 %), followed by essential hypertension (15.5 %). In children with essential hypertension, obesity/overweight was the most common risk factor, observed in 72.2 % of patients, followed by family history of hypertension (44.4 %). Hypertensive urgency and emergency were seen in 14 (13.3 %) and 6 (5.7 %) patients. Conclusion: There has been a substantial increase in the proportion of essential hypertension among children and a significant rise in the incidence of overweight/obesity among children with essential hypertension. Timely screening, lifestyle alterations, and effective care are essential for reducing long-term problems related to paediatric hypertension.